Effect of Different Fruit Sizes on Storage Period and Fresh Weight Loss of Forage Watermelon (Citrullus lanatus var. citroides) - GEREN, Hakan (MAS Journal of Applied Sciences, 2024)
This study was carried out to evaluate the effects of different fruit sizes on storage period and fresh weight losses in forage watermelon (Citrullus lanatus var. citroides) under the ecological conditions of Tire-Izmir in 2021 and 2022. In the study, Turkmenistan originated forage watermelon genotype was used as plant material. The field experiment was set up randomized block design with three replications. In the study, some properties were measured such as fresh fruit yield (t ha-1), peel thickness (mm), Soluble solid content (%) and fresh weight losses (%) were examined. After harvest, the fruits were divided into three groups: large [(L)>7 kg], medium [(M) 4-7 kg] and small [(S)<4 kg] fruits. The fruits were stored under traditional warehouse conditions for 12 months. Two-year average results showed that forage watermelon is quite well adapted to local conditions. Year effect was significant on the yield and some yield components of forage watermelon. Storage period and fruit size were also significant effect on fresh weight loss. As storage period extended fresh weight losses increased, and, losses in large fruits were higher than in medium and small fruits.